EVITA: Computational model for evaluating buildings thermal efficiency - Almao, Nastia; Rincón, José; González, Eduardo (Rev. Téc. Fac. Ing. Univ. Zulia, 2011)
In this paper the details of a two-dimensional computational model named “EVITA” are presented. It has been developed to simulate and evaluate the thermal performance of a building section. The model is based on the finite volume approach, with a collocated arrangement of variables, and a bounded high order treatment of the convective terms. The algorithm used to solve the two-dimensional transient form of the coupled equations of Continuity, Momentum and Energy is a PISO-Iike scheme. The calculation domain is a rectangular section of a construction over which the grid is built, such that it considers any material composition for walls, roof and floor, under transient boundary conditions: ambient temperature, relative humidity, global irradiance on the envelope, long wave radiative exchange between external surfaces and sky, soil temperature and the average wind velocity. The convective motion of the air inside the section is simulated using the Boussinesq approximation. With the inherent restrictions of a two-dimensional analysis, this model has been validated, and therefore, it can be considered as a high precision tool to make building thermal performance simulations.